2009
DOI: 10.1002/crat.200900126
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐sized silver crystals and their dispersion over α‐alumina for ethylene epoxidation

Abstract: Ethylene oxide catalyst is a high metal loading catalyst, in which silver crystals is impregnated on α-Al 2 O 3 support. In this type of catalyst, metal dispersion plays an important role on catalyst selectivity for desired products. In this work, silver nitrate and silver oxide together with oxalic and lactic acid as the raw materials were used with different impregnation techniques to make catalysts with high silver content and dispersion. It is also known that the use of promoters affect the metal dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Previous work showed that the dispersion of Ag, the morphology and temperature treatment of the support all affect, besides operational parameters, the performance of the catalyst. [336][337][338] It is also possible that the exposed surface of SrFeO 3 is largely responsible for non-selective oxidation reactions and the activity of the oxide substrate to catalyze nonselective oxidation reactions should not be overlooked. Another challenge observed by Chan et al was the low rate of oxidation when the redox catalyst was regenerated in air, causing a gradual loss in oxygen capacity.…”
Section: View Article Onlinementioning
confidence: 99%
“…Previous work showed that the dispersion of Ag, the morphology and temperature treatment of the support all affect, besides operational parameters, the performance of the catalyst. [336][337][338] It is also possible that the exposed surface of SrFeO 3 is largely responsible for non-selective oxidation reactions and the activity of the oxide substrate to catalyze nonselective oxidation reactions should not be overlooked. Another challenge observed by Chan et al was the low rate of oxidation when the redox catalyst was regenerated in air, causing a gradual loss in oxygen capacity.…”
Section: View Article Onlinementioning
confidence: 99%
“…From previous studies it is clear that properties of the final catalysts are significantly dependent on both the silver precursor and the preparation method employed. 8,9 Metallic silver catalysts can be prepared by reduction of a variety of precursors including its oxide, [10][11][12] nitrate, 9,13 oxalate, 14,15 lactate, 16 and other salts (e.g. silver neodecanoate 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Silver oxalate is a particularly attractive precursor for large-scale production of silver catalysts as it can be dissolved in organic amines giving solutions with a concentration as high as 30 wt % (based on Ag). 8 In commercial catalyst production with silver oxalate as silver precursor, calcination is used to form supported metallic silver nanoparticles, which is a thermal decomposition (activation) process. So far little study on the thermal decomposition process was publicly and deeply reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nanometer-sized noble metals are of great interest not only for their unique properties [1][2][3], but also for their potential applications in the fields of biomedical diagnostics [4], catalysis [5], optical devices [6], and data storage [7]. Among them, silver nanomaterials are particularly interesting due to their roles as substrates in studies of the surface-enhanced Raman scattering [8,9], nonlinear optical properties [10], and catalysis [11]. For the optical properties, absorption associated with the collective oscillation of the conduction electrons or surface plasmon resonance (SPR) has been studied for many decades.…”
Section: Introductionmentioning
confidence: 99%